Union Solidarity in Eastern and Central Europe from the Example of Poland - Bomba, Katarzyna (University of Wroclaw. Faculty of Law, Administration & Economics, 2016)
This study examines the extent of union solidarity in post-communist European countries using the example of Poland. It shows the process of the transition of trade unions from being mass organisations with a mandate from the state to voluntary organisations defending employees’ rights and interests within the social dialogue with the state and employers. It argues that the current legal regulations of decentralised institutions in Polish and other Eastern and Central European countries impede union solidarity. The reasons behind the crisis of trade unions are numerous and complex. They have been seen especially in the changes of the structures of enterprises, from large state-owned entities to small and medium-sized enterprises (SMEs). It can also be seen in the use of collective bargaining policies and the role of the state in industrial relations. It examines the role of non-union representations on the labour market and their chances of replacing trade unions or cooperating with them. The paper concludes that instead of searching for unlikely solutions to change the model of bargaining or replacing trade unions with other forms of employee representations, solutions in favour of strengthening the social position of trade unions through improving the existing trade unions' legal framework should be sought.
Keywords: związek zawodowy; solidarność związkowa; multiprzedsiębiorstwa; globalizacja; kraje postkomunistyczne